SPLENIC ANGIOGRAPHIC EMBOLIZATION IN IV AND V-GRADE SPLENIC INJURIES. DOES IT WORK? OUR EXPERIENCE ON THE MANAGEMENT OF SPLENIC INJURIES IN THE LAST 14 YEARS. (18th May 2021) - Lucas Guerrero, V; Montmany, S; Rebasa, P; Luna, A; Navarro, S
Abstract: INTRODUCTION: Spleen is frequently damaged in abdominal trauma. Patients with splenic injury with hemodynamic instability, peritonism signs or other surgical injuries need emergent surgery. Hemodynamically stable patients are treated conservatively. Splenic embolization is indicated in injuries with blush, pseudoaneurysms or arteriovenous fistulas. It is unclear its indication in IV and V-grade splenic injuries without contrast extravasation. Our hypothesis is that IV and V-grade splenic injuries embolization decreases conservative treatment failure. MATERIAL AND METHODS: Retrospective observational study, including all patients with blunt splenic injuries, prospectively included in our registry of polytraumatic patients (>16 years) since 2006. RESULTS: One hundred and seventy patients have been included since 2006. In 2006-2013, when splenic injuries with active bleeding, pseudoaneurysms or arteriovenous fistulas were embolized, 94 patients were included. 37, 2% required surgery and 62, 8% conservative treatment. Splenic embolization was performed in 17% of patients who were treated conservatively. Conservative treatment failure was 16, 9%: 10 cases out of those who underwent medical treatment (4 required embolization and 6 needed surgery). From 2014 to the present, when IV and V-grade injuries were included in the indications for embolization, 76 patients have been included. 38, 2% required surgery and 61, 8% were treated conservatively (40, 4% were embolized and the rest were treated medically). One case (3, 6%) of those treated medically and another (5, 3%) of those embolized failed. Overall failure of conservative treatment was 4, 3%. CONCLUSION: Embolization of IV and V-grade splenic injuries decreases conservative treatment failure from 16, 9% to 4, 3%.